Análisis físico organoléptico de la elaboración de albóndigas a base de sardinas y jurel del puerto de huanchaco, usando verduras del valle santa catalina. - Enco Iparraguirre, Michel Charly (2011)
The summary deals with the production of canned sardines, caught in the ports of Huanchaco, Delicias, for which vegetables were used, which are produced in the Santa Catalina Valley. The general flow begins with receipt of the fish, which are washed, headless, filleted and chopped and drained after washing is homogenized, pour the dressing is previously prepared based on vegetables and seasonings. It was used in vegetables: onions, peas, parsley, caihua, chili, which are also washed, peeled, cut and subjected to boiling point, then are cooled to prevent overcooking. It being the homogenized mass proceed immediately to fill caihua and other vegetables, using manual action tablespoons, tending the break crack berries. It is then packaged into account the weight taking and size of it, after the cans are placed in the cooker, organoleptically to be evaluated; after a time 30 days at room temperature.